Newly Discovered Circumstances in Administrative Legal Proceedings of Ukraine - BIELOVA, Olena; ROMANENKO, Yevgeniy; KAYDASHEV, Roman (Journal of Advanced Research in Law and Economics, 2017)
The article is devoted to identifying theoretical problems and to studying the practice of application of Chapter 4 of Section IV of the Code of Administrative Court Procedure of Ukraine during consideration and resolution of administrative cases that are considered by courts in connection with newly discovered circumstances. A definition of the term ‘newly discovered circumstances’ is proposed. The content of the notion ‘circumstances essential for a case’ is explored. The practice of consideration by administrative courts of cases of judicial review under paragraph 1 of Part 2 of Article 245 of the CAP of Ukraine depending on the subject of filing the application is analyzed. It is proved that the avoidance of ambiguous understanding the concept of newly discovered circumstances, to include with them the legal facts that are essential to resolve the case on the merits (that is, give rise to certain procedural consequences) and that existed during the primary proceedings and passing the judicial act, but were not and could not be known both to the parties and the court, on the assumption of fulfillment by them of all legal requirements for unbiased, full, and comprehensive consideration of the case and passing a legitimate and reasonable judgment.